Age model of a sediment core from Rio Grande Rise - Marina Arbex de Castro Lima; Maria Aline Lisniowski; Ana Luiza Albuquerque; João M Ballalai; Laercio Lopes Martins; Narelle Maia de Almeida (PANGAEA, 2025)
An 11 cm sediment core was collected during the PROERG-AMB VIII expedition of the Geological Survey of Brazil (SGB) in 2023, on board the research vessel NPqHo Vital de Oliveira, in a region adjacent to the western part of the Rio Grande Rise, in the western South Atlantic. A flat relief characterizes the area. The core was collected using a box corer at a depth of 3,287 m, and the performed analysis aims to reconstruct the variation in paleoenvironmental conditions, such as temperature and carbonate dissolution, throughout the Holocene and late Pleistocene, contributing to the investigation of climatic variations in the South Atlantic. The core was sampled at 1 cm intervals, providing 11 samples. About 500 Globigerinoides ruber specimens were picked from depths of 1, 4, 8, and 11 cm destined for radiocarbon (14C) analysis in the Accelerator mass spectrometry (AMS) from the Poznan Radiocarbon Laboratory (Poznan, Poland). Conventional ages were converted to calibrated ages using the Marine20 calibration curve (Heaton et al., 2020) without any regional reservoir age correction (ΔR). The calibration and age model construction were performed by interpolating the four radiocarbon ages using Bayesian Inference Gaussian Process regression and Multiproxy Alignment of Continuous Signals (BIGMACS) package performed in MATLAB software, which produced an average sedimentation rate of 1 cm/ka, allowing the core to extend approximately to 15 ka.